MATHEMATICAL TEACHING IN ESCOLA NORMAL DE CAETITÉ-BAHIA (1926-1961): SOME TEXTBOOKS - Araújo, Fabrícia Oliveira de (2020)
In this article, one presents a brief historical overview of the results of the master's research that proposed to study knowledge in the mathematical formation of students of Escola Normal de Caetité-Bahia (1926-1961). This time frame refers to the period of existence of that school. This is a historical research from the perspective of cultural history according to Roger Chartier, and the analyses incorporate discussions by theorists who approach concepts of School Culture (Dominique Julia) and knowledge to teach and knowledge for teaching (Rita Hofstetter and Bernard Schneuwly). In this context, one observed that the internalization of the offer of teachers formation course, through the creation of Escolas Normais in the State of Bahia, has made possible for the city of Caetité to host a teaching unit in this modality. And, having as interest to investigate how the formation processes in the scope of mathematics happened, it is that, through the mathematics textbooks used in this institution, one observed that knowledge related to algebra, geometry, statistics, and, mainly, arithmetic, as well as knowledge about the intuitive method, new school and traditional mathematics teaching were contemplated to some extent.